Entrepreneurship-Based Education: Teaching Students to Think Creatively and Innovatively - Wakhudin Wakhudin; Hasan Basri; Andri Wahyudi; Martin Anjar Ginanjar (PT. Anagata Sembagi Education, 2024)
Entrepreneurship-based education in the era of globalization and fast-developing technology is becoming increasingly important for the younger generation to face the challenges of a dynamic world of work. The purpose of this study is to explore the effectiveness of entrepreneurship education in shaping an innovative mindset among students. The methods used in this study include qualitative analysis through a literature review approach to analyze and summarize various relevant sources on entrepreneurship education and the development of creative and innovative thinking skills in students. The results showed that entrepreneurship-based education successfully improved students' skills in identifying opportunities, solving problems creatively, and adapting to change. The implication of this study confirms that the integration of entrepreneurship education in the curriculum can significantly contribute to the development of relevant skills for students, as well as encourage innovation and economic growth in society. Further research is recommended to explore different approaches in teaching entrepreneurship and their impact on students' long-term development.